The Effect of Using Anagram in Learning Vocabulary in SMPN 1 Teluk Mengkudu - Sinaga, Dolli Rotua; Siburian, Eviliana Bintuari; Silaen, Rohani (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aimed to find out the effect of using anagram in learning vocabulary in SMP N 1 Teluk Mengkudu during the 2023/2024 academic year. The subjects of this study were two second-semester classes, each with 32 students. The research employed a quantitative method with an experimental design. The data collection procedures were divided into three parts: pre-test, treatment, and post-test. The data were analyzed by scoring each of the two groups' papers, with each correct answer from 20 questions receiving one point. The hypothesis was confirmed as the t-observation value was higher than the t-table value (2.046 > 1.670) at a significance level of alpha 0.05 and a degree of freedom (df) = 62. It can be concluded that teaching students using anagram significantly affects their vocabulary learning.